Desain Pembelajaran Refleksi dan Translasi Berkonteks Klenteng Sam Poo Kong Semarang - Aidha Aprilia Puji Lestari; Aryo Andri Nugroho; Farida Nursyahidah (Universitas Hamzanwadi, 2021)
Reflection and translation material are critical to be mastered by students in learning transformation material. However, reflection and translation material are still difficult for students to understand. Therefore, this study aims to develop a learning trajectory that will assist ninth-grade students of Junior High School in grasping the notion of reflection and translation in the context of the Sam Poo Kong Temple in Semarang. The research used the design research method, which consisted of three stages: the preliminary design, the design experiment (pilot experiment and teaching experiment), and retrospective analysis. The PMRI approach was used to develop learning activities in this research. This study involved 32 ninth-grade students at a junior high school in Semarang city. The results of this study is a learning trajectory that includes a series of learning processes in four activities. These are observing the Sam Poo Kong Semarang video and analyzing the properties of reflection, finding the reflection formula, analyzing the properties of translation, discovering the translation formula, and solving contextual problems related to reflection and translation. The activities conducted can enable students to develop a better understanding of material reflection and translation. The research's findings indicate that using the Sam Poo Kong Semarang temple context can equip ninth-grade students to comprehend the concept of material reflection and translation. Additionally, the outcome of this study offers additional local wisdom options that can be used as a context in mathematics.